Egg production of Austropandalus grayi (Decapoda, Caridea, Pandalidae) from the Magellan Region, South America - Wehrtmann, Ingo S.; Lardies, Marco A. (Scientia Marina, 1999)
Austropandalus grayi is one of three pandalid shrimp species reported from Chilean waters. Here we describe fecundity, reproductive output, and chemical composition of the incubated embryos of A. grayi, providing the first account of such information for a pandalid species inhabiting the southern hemisphere. Ovigerous females (n = 96) were collected during October - November 1994 with an Agassiz trawl in waters off Patagonia and Tierra del Fuego, South America. Both egg production (between 50 and 1858 embryos) and early egg volume (x- = 0.069 mm3) of A. grayi were low when compared to values reported from other pandalids. Clutch size increased with maternal size, however, the size of recently-spawned eggs was not linked to female size. Although the egg mass volume remained almost stable during the incubation period, females lost on average 51.1% of their initially-laid embryos; however, this loss was more than compensated by an 88.4% increase of the egg volume during embryogenesis. Mean reproductive output was relatively low (0.133) and not related to maternal size. The RO-data of A. grayi and other pandalids seem to indicate an increasing energy allocation for reproduction towards higher latitudes, a trend which would be contrary to the results of studies with other crustaceans. Water was the predominant constituent of the chemical composition of developing embryos and increased from 62.2% to 70.2% during the incubation period. At the same time, organic matter declined and mineral content augmented. Generally, our results are in agreement with previous findings with regard to the chemical composition of developing decapod embryos.